PENTINGNYA IMPLEMENTASI NILAI PANCASILA SILA KESATU DALAM MENUMBUHKAN KARAKTER SISWA SEKOLAH DASAR – ANALISIS STUDI PUSTAKA - Diana Aliansyah Sopia; Mayang Avrilla; Robi Anawiyah Sya’bani (STKIP Subang, 2023)
The application of Pancasila values ​​is very important in developing the character of elementary school students in everyday life. The application of the values ​​in the first precepts of Pancasila is based on